EFFECT OF DIFFERENT FEED RESTRICTION REGIMES ON GROWTH PERFORMANCE AND ECONOMIC EFFICIENCY OF JAPANESE QUAILS - Y. Abbas; A. W. Sahota; M. Akram; S. Mehmood; J. Hussain; M. Younus; M. M. Awais; A. R. Sial (Journal of Animal and Plant Sciences, 2015)
The present study was executed to examine the growth performance and economic efficiency of Japanese quail (Coturnix coturnix japonica) at Avian Research and Training (ART) Centre, UVAS, Lahore. For this purpose a total of 3200 quail chicks were allocated to four different feed restriction regimes comprising four close-bred stocks (Imported, Local-1, Local -2 and Local-3) at the age of 10 days. The experimental quails in group 1 were fed ad-libitum (20.30% CP, 1.3% Lysine) diet throughout the experimental period to serve as control while groups 2, 3 and 4 were provided with 1 hour feed- 3-hour off, 2-hour feed- 2hour off and 3-hour feed-1hour off feeding regimes, respectively. Weekly data on growth parameters were recorded. Maximum feed intake was observed in ad-libitum fed group whereas the highest body weight gain was observed in ad-libitum and 3 hour fed quails. The best FCR leading to maximum profit margin was observed in 3 hour-fed group. However, different close-bred stocks could not express any significant difference in growth parameters.
Keywords: Feed restriction regimes; Growth performance; Economic efficiency; Japanese quails